Implementasi Asas Good Governance di Indonesia dalam Perspektif Fiqh Siyasah Qadaiyyah - priyo handoko (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2020)
This study purpose to describe the implementation of the principle of good governance in the justice system in Indonesia. It will also be explained in relation to the view of fiqh siyasah qadaiyyah in the application of the principle of good governance in the world of justice. The research method used is normative legal research, through a legislation and conceptual approach that is expected to be able to answer and provide a description of this research. The results of the study say that the application of the principle of good governance in the world of justice can begin by applying transparency and accountability in each court institution. In addition, fiqh siyasah  qodloiyah in Islamic justice also strongly recommends that judges always do justice and deliver the mandate as well as possible. Therefore, both in the Islamic court and the judiciary in Indonesia have both applied the principles and principles of good governance.